Neural Correlates of Quality During Perception of Audiovisual Stimuli - Arndt, Sebastian; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book presents a new approach to examining perceived quality of audiovisual sequences. It uses electroencephalography to understand how exactly user quality judgments are formed within a test participant, and what might be the physiologically-based implications when being exposed to lower quality media. The book redefines experimental paradigms of using EEG in the area of quality assessment so that they better suit the requirements of standard subjective quality testings. Therefore, experimental protocols and stimuli are adjusted accordingly. .
Motivation -- State of the Art -- Short-Term Experiments -- Long-Term Experiments -- Medium-Term Experiments -- Discussion and Conclusion.
Keywords: Engineering; User interfaces (Computer systems).; Electrical engineering; Neuropsychology; Engineering; Communications Engineering, Networks; User Interfaces and Human Computer Interaction; Neuropsychology; Electronic books